Under The Shadow of Sharia: Christian Muslim Relations from Acehnese Christian Experience - Ansor, Muhammad; Arrauf, Ismail Fahmi; Amri, Yaser (Universitas Negeri Semarang, 2016)
The implementation of sharia in Aceh has have given a complex impacts to several aspects of life of the Christian, economically, culturally, politically and any other aspects of social life. Unlike other Indonesian Christian in different parts of archipelago, the Christian women in Aceh are experiencing the life that regulated by the sharia. Based on the experience in Langsa, some of them (especially teachers, employee, and students) were appealed to wear headscarf (hijab) in their appearance in Islamic public sphere. Those who reside in Aceh Singkil experienced difficulties in establishing church, beyond any difficulties that experienced by Christians in other part of Indonesian region. However, in Southeast Aceh, the Christian live the life of religious harmony among the Muslim majority who implement the Islamic sharia. This article shows that strong encouragement among the Muslim circle to implementing Islamic sharia through political approach could generate difficulties to certain Christians, while to some others it doesn't give any significant negative impact. This article aims to highlight some issues that experienced by Christians who live amid the Muslim majority who implement Islamic sharia. Data were collected during ethnographical studies conducted in the year 2013-2015 in Langsa, Aceh Singkil and Southeast Aceh. Finally, this article proposes significant policy options for managing Muslim-Christian relations in Aceh, Indonesia. Education is crucial for promoting interreligious harmony, religious freedom, and respect for people of different traditions and religion.